FAKTOR-FAKTOR YANG MEMPENGARUHI NILAI PERUSAHAAN DENGAN PROFITABILITAS SEBAGAI PEMODERASI - Chandra, Felisia Shendy; Hastuti, Rini Tri (Jurnal Paradigma Akuntansi, 2024)
This study aims to obtain empirical evidence regarding the effect of dividend policy and leverage with profitability as moderating variable on firm value. The final sample used in this study amounted to 38 manufacturing companies listed in Indonesia Stock Exchange, obtained by purposive sampling method. The data that has been collected by Microsoft Excel 2019 software and then processed using EViews 12 software. The results show that the variable of dividend policy has no effect on firm value. Meanwhile, leverage has a significant positive effect on firm value. And for the profitability as moderating variable, profitability isn’t able to moderate the influence between dividend policy and leverage on firm value variable.